Direct dynamic measurement of intracellular and extracellular lactate in small‐volume cell suspensions with 13C hyperpolarised NMR. (30th June 2015) - Breukels, Vincent; Jansen, Kees (C.) F. J.; van Heijster, Frits H. A.; Capozzi, Andrea; van Bentum, P. Jan M.; Schalken, Jack A.; Comment, Arnaud; Scheenen, Tom W. J.
<x xml:space="preserve">Abstract</x> Hyperpolarised (HP) 13C NMR allows enzymatic activity to be probed in real time in live biological systems. The use of in vitro models gives excellent control of the cellular environment, crucial in the understanding of enzyme kinetics. The increased conversion of pyruvate to lactate in cancer cells has been well studied with HP 13C NMR. Unfortunately, the equally important metabolic step of lactate transport out of the cell remains undetected, because intracellular and extracellular lactate are measured as a single resonance. Furthermore, typical experiments must be performed using tens of millions of cells, a large amount which can lead to a costly and sometimes highly challenging growing procedure. We present a relatively simple set‐up that requires as little as two million cells with the spectral resolution to separate the intracellular and extracellular lactate resonances. The set‐up is tested with suspensions of prostate cancer carcinoma cells (PC3) in combination with HP [1‐13C]pyruvate. We obtained reproducible pyruvate to lactate label fluxes of 1.2 and 1.7 nmol/s per million cells at 2.5 and 5.0 mM pyruvate concentrations. The existence of a 3‐Hz chemical shift difference between intracellular and extracellular lactate enabled us to determine the lactate transport rates in PC3. We deduced a lactate export rate of 0.3 s−1 and observed a decrease in lactate transport on addition of the lactate transport inhibitor α‐cyano‐4‐hydroxycinnamic acid. Copyright © 2015 John Wiley & Sons, Ltd.